Code-Switching Elicitation Task in Standard Arabic, Dialectal Arabic, and English Among Bilingual Saudi Arabian Students in the United States - Bahri, Sharifa (International Journal of Linguistics, 2022)
This study explores code-switching practices among bilingual Saudi Arabians within three language varieties: English, Standard Arabic (SA), and Dialectal Arabic (DA). While there are studies that examine the use of code-switching between SA and DA, and others that investigate Arabic-English code-switching, no study to date has examined natural code-switching into English in conversations of SA vs. DA as compared to code-switching into Arabic in English conversations. Controlling the language of the interviewer (English, SA, or DA), this study examines (1) the likelihood of code-switching relative to the language of the interview, (2) the rate of switches in each interview context, and (3) the mean duration of those switch segments. Results show that code-switching to Arabic was very rare in English interviews (only 0.89% of interview time was in Arabic with a switch rate of 1.74 switches/minute and average length of 0.59 s). However, participants in SA and DA interviews did code-switch to English 8.32% and 10.08% of the time, respectively. The mean rate of switches was about twice as frequent for participants interviewed in DA (14.18 switches/minute) than for participants interviewed in SA (7.21 switches/minute). Moreover, participants in SA interviews had significantly longer mean English segments than DA interviewees (1.21 s vs. 0.81 s, respectively). The results demonstrate that (1) English has the greatest impact on participants’ tendency to code-switch, (2) SA encourages code-switching in a way that aims to preserve its formal status, and (3) DA encourages code-switching the most, i.e., code-switching is an emblem of DA conversations.